Study of Power Frequency Overvoltage Suppression on UHV Transmission Line - HAN Mengmeng; WU Wenhui; HUANG Kan; WAN Liqin (Kongzhi Yu Xinxi Jishu)
It mainly studied the improvement measures of overvoltage level for UHV transmission line from Jindongnan to Jingmen. It analyzed single-phase grounding load shedding overvoltage and fault-free load shedding overvoltage in the case of the single operation mode based on the ATP simulation. The measures of overvoltage limit were accordingly presented and the best one was proposed through comparison of the pros and cons of all the measures based on different reactive power compensation points in EMTP simulation. The results show that the operation modes in various compensation methods selected from all segments of the whole line have a certain effect on the overvoltage suppression.